Digitization Of School Administration - Azizah, Habib Nun; Leksono, Tito Panji; Prestiadi, Dedi; Syaiful, Syaiful; Nurani, Budi (Proceedings Series of Educational Studies, 2024)
The rapid development of technology and digitization of information systems has encouraged all aspects of community life to change. One of the aspects affected by this development is the education sector. Attendance is a fundamental element in maintaining school discipline and accountability, therefore, the development of technology that can facilitate the attendance process is urgently needed. This article uses literature studies obtained from journals and preconceived online books. In its implementation, administrative digitization in the education system in Indonesia has a significant impact. One of them is in the field of attendance, the digitization of the attendance system is a breakthrough that is very appropriate in the current era. With digital presence, school data collection has become easier. One example of application development in the field of education is "SI-PRODI" and others. Keywords: digitalization; psession; innovation